Analysis of the influence of viscosity to the liquid film flow between two plates - Muhammad Azdnan, Amat (2016)
This thesis deals with analysis of the influence viscosity to the liquid film flow between two plates. How the different viscosity of liquid film can lead to the time taken to full-filling the gap between the two plates? What is the filling pattern of the liquid film upon flowing through the gap? Thus, the objective of this thesis are to analyze the time taken for liquid to full filling the gap between two plates influenced by different liquid viscosity and visualize the flow pattern of the liquid flow upon flowing through the gap between two plates. The procedures to do this project state as following. The two plates of glasses are prepared and the length and width of both plates are measured. The gap between the two plates is set to 50 μm, approximately by using double sided-tap. Then the liquid with 1cSt is sucked by syringe. After that the liquid is injected into the gap. The time taken is recorded to filling up the gap. In addition, the video is taken during the process of liquid film advancement. The experiment is repeated for two more times to get the average time taken and liquid film behavior is observed during the filling up process. The procedure is repeated with 100 cSt, 800 cSt and 10000 cSt of liquid. From the results, it is observed that the analysis with helping of Video to JPEG converter Software and Photoshop Software yields more accurate data then. Ho just using only stopwatch and scaling ruler. The acquired results show the relationship between viscosity and filling time and distance travelled under 10 seconds. The liquid with 1 cSt which is the most lowest produced shortest time taken compared to 100 cSt, 800 cSt and 10000 cSt. While the most higher liquid viscosity that is 10000 cSt would had shortest distance travelled of flow advancement within 10 seconds. On top of that, the preliminary results in determining liquid volume used really important in order to optimize the utility of using liquid viscosity. For the experiments, 3 ml of volume of liquid is the optimum volume for the liquid viscosity to flow between two plates stress. The obtained results indicate that the flow pattern of each liquid viscosity can be different. However, the ideal flow pattern showed in this thesis. The results concluded that the viscosity and flow pattern are affects the flowing liquid between two plates. Therefore, viscosity played a vital role for study the liquid flow for underfill process. The results can also significantly reduce the cost and time to market, and improve product reliability and sustainability.